2021
DOI: 10.3389/fpsyg.2020.612424
|View full text |Cite
|
Sign up to set email alerts
|

Transgender Identity Is Associated With Bullying Involvement Among Finnish Adolescents

Abstract: BackgroundDuring adolescence, bullying often has a sexual content. Involvement in bullying as a bully, victim or both has been associated with a range of negative health outcomes. Transgender youth appear to face elevated rates of bullying in comparison to their mainstream peers. However, the involvement of transgender youth as perpetrators of bullying remains unclear in the recent literature.ObjectiveThe aim of this study was to compare involvement in bullying between transgender and mainstream youth and amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 64 publications
(103 reference statements)
0
20
0
Order By: Relevance
“…Regarding bullying, several studies [ 1 , 2 , 5 ] showed that gender identity is a risk that influences bullying and/or violence at school. This bullying is characterized by teasing, insults, and physical aggression.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding bullying, several studies [ 1 , 2 , 5 ] showed that gender identity is a risk that influences bullying and/or violence at school. This bullying is characterized by teasing, insults, and physical aggression.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the pedagogy of containment, it is important to reflect on the protection of identified students since such students will always be likely to be questioned and have to suffer the consequences of existing in today’s society. Other studies [ 1 , 2 ] have discussed the consequences affecting the well-being of victims, such as decreased confidence, decreased ability to trust the people around them, and suicidal thoughts. Regarding the prevention of gender-based violence and harassment, there are still only a few existing programs (even less in terms of prevention in the case of transgender people), with empathy being a key variable as considered in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, for children and adolescents formulating their senses of self and others, it is especially vital to identify and connect with their own gender identity. Because of the societal power relations connected to GISA, persistent discomfort with socially expected gender typicality creates impediments for adolescents' emotional and social development (Hepp et al, 2005;Rieber, 2006;Diamond, 2013), and transgender adolescents have been shown to be bullied and to perpetrate bullying at elevated rates (Heino et al, 2021). As well, gender diverse adolescents' self-concept (e.g., self-esteem), emotional stability (e.g., emotional styles, dissociation, anxiety, and depression), and positive social relations to their peers (e.g., social competence and social desirability), which are crucial for their development, are identified as under pressure and subjected to special health care treatments (Baams, 2018) while the societal power relations leading to exactly these symptoms (Hoshiai et al, 2010) are mostly not addressed (Eisenberg et al, 2017).…”
Section: Identifying Gender Identity Empiricallymentioning
confidence: 99%